Ionic diffusivity of manganese-based spinel-layered composite nanoarchitectures: An analysis of morphological dependence - Ledwaba Raesibe; Ngoepe Phuti (MATEC Web of Conferences)
The electrochemical performance of spinel LiMn2O4 has been demonstrated to vary depending on the morphology of the electrode material. Lithium-ion battery development and optimization require a thorough understanding of the diffusion of lithium ions in electrode materials. Modifying the microstructure of the LiMn2O4 by controlling the distribution and compactness of particles can improve electrochemical properties. This interest in spinel is driven by its enormous appeal as a cathode material due to its robust structure with a three-dimensional ion transport channel, high operating voltage (~4.7 V versus Li+/Li), and its use in high-energy lithium-ion batteries. The Mn-rich chemical composition renders it more economically benign considering the abundance of Mn-raw materials. In this study, we elucidate the impact of morphology on electrochemical ionic kinetics of the simulated nanoarchitecture materials by utilizing molecular dynamics simulations from 300K to 2000K. Analysis of the diffusion coefficients demonstrates that the nanospherical particles display dominant ionic diffusivity compared to 2D-nanosheets and 3D- nanoporous morphology. Ultimately, the volumetric and surface analysis demonstrates the robustness of nanoporous morphology as they are reported as 5% and 1%, respectively. These findings demonstrate that the nanoporous morphology has a robust structural integrity.